2008
DOI: 10.1080/03014460802575633
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous fat stores related to weight in full-term neonates

Abstract: The study provides a new perspective to the idea that fat storage increases continuously during the last period of gestation. The data presented showed that this phenomenon is not clearly demonstrated for full-term infants with appropriate weight for GA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
(30 reference statements)
4
10
0
Order By: Relevance
“…Body weight and length are greater in males, whereas subscapular and tricipital skinfold thicknesses are greater in females (7)(8)(9). Consistent with these findings, our study population showed higher weight and BMI and longer length among male infants (Figure 4).…”
Section: Effect Of Protein Intake and Sex On Anthropometric Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…Body weight and length are greater in males, whereas subscapular and tricipital skinfold thicknesses are greater in females (7)(8)(9). Consistent with these findings, our study population showed higher weight and BMI and longer length among male infants (Figure 4).…”
Section: Effect Of Protein Intake and Sex On Anthropometric Parameterssupporting
confidence: 93%
“…It is well known that growth and body composition differ between sexes from an early age (7,8). Girls have more fat mass and less lean body mass, are shorter, and weigh less than do boys (9).…”
Section: Introductionmentioning
confidence: 98%
“…In the present study, multiple linear regression analysis found that ESS scores significantly correlated to maternal employment status and arm circumference and neonatal birth weight. As others have observed [27,28], an increased maternal arm circumference (indirect measure of gestational weight gain) and neonatal birth weight may relate to an increased uterine fundus which exerts a ventilatory limitation that favors sleep disorders and sleepiness.…”
Section: Discussionmentioning
confidence: 92%
“…Pre-pregnancy BMI was calculated as body weight (kg) divided by height (m) squared. BMI of participants were categorized according to internationally accepted cut-off points as low (\18.5 kg/m 2 ), normal (18.5-24.99 kg/m 2 ), or high (C25 kg/m 2 ) Women with high BMI were further categorized as being overweight (25)(26)(27)(28)(29).99 kg/m 2 ) or obese (C30 kg/m 2 ) [18]. Pregnancy weight gain was calculated as weight (kg) at survey minus pre-pregnancy weight.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…To further investigate the relationship between birth weight and neonatal anthropometry, gestational age- and sex-adjusted standardised residuals were first derived for the variables using multiple regression, given evidence for differences in birth weight, body composition and body size/proportions along these lines [38][41]. Stepwise multiple regression of anthropometry residuals on birth weight residual was then performed.…”
Section: Methodsmentioning
confidence: 99%